Masking Strategies in Kierkegaard and Kafka. A Brief Reflection on the Role of the Writer on Modern Bourgeois Society - Bartoli, Fabio (2021)
This article discusses the masking strategies that Kierkegaard and Kafka adopted throughout their lives. Firstly, some features of bourgeois society and the role that the writer had within it are analyzed. Subsequently, Kierkegaard’s communication strategy is described, and its ends are identified; after that, we follow the same procedure with the case of Kafka. Finally, the two positions are compared, underlining differences and similarities to use the results as elements for a brief reflection on the role of the act of writing in modern bourgeois society.